2008
DOI: 10.2166/wst.2008.039
|View full text |Cite
|
Sign up to set email alerts
|

The potential of bio-methane as bio-fuel/bio-energy for reducing greenhouse gas emissions: a qualitative assessment for Europe in a life cycle perspective

Abstract: Anaerobic digestion is a well known process that (while still capable of showing new features) has experienced several waves of technological development. It was "born" as a wastewater treatment system, in the 1970s showed promise as an alternative energy source (in particular from animal waste), in the 1980s and later it became a standard for treating organic-matter-rich industrial wastewater, and more recently returned to the market for its energy recovery potential, making use of different biomasses, includ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
25
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 76 publications
(26 citation statements)
references
References 1 publication
0
25
0
Order By: Relevance
“…In the USA there are 650 sewage sludge digesters, 106 of which had gas utilisation (Kalogo and Montieth, 2008). The European Commission has reported that the AD of domestic waste (sewage sludge and the organic fraction of municipal solid waste) could in theory provide 3% of Europe's energy needs (Tilche and Galatola, 2008) and the UK government has announced a strategy to encourage the uptake of AD as a source of renewable energy (DEFRA, 2011). Increased use of AD is an opportunity for the water industry because of their experience and integration within existing WWT.…”
Section: Introductionmentioning
confidence: 99%
“…In the USA there are 650 sewage sludge digesters, 106 of which had gas utilisation (Kalogo and Montieth, 2008). The European Commission has reported that the AD of domestic waste (sewage sludge and the organic fraction of municipal solid waste) could in theory provide 3% of Europe's energy needs (Tilche and Galatola, 2008) and the UK government has announced a strategy to encourage the uptake of AD as a source of renewable energy (DEFRA, 2011). Increased use of AD is an opportunity for the water industry because of their experience and integration within existing WWT.…”
Section: Introductionmentioning
confidence: 99%
“…Thereby, biogasification using energy crops is the only fuel-producing process with a closed CO 2 and nutrient cycle (8). The production of biogas from plant waste or other organic materials is a feasible strategy in view of both ecology and economy (63). Fodder beet was chosen as the renewable biomass source for a thermophilic biogas fermentor because the European Union decreased the regulatory price for sugar beets in 2006, and therefore many farmers are looking for an alternative use.…”
mentioning
confidence: 99%
“…Biogas can be applied on different scales with small scale domestic biogas application for cooking, or large scale industrial application with biogas use for electricity production. Upgraded biofuel can furthermore be used as transport fuel as widely implemented in Sweden (Borjesson and Ahlgren 2012;Tilche and Galatola 2008).…”
Section: Introductionmentioning
confidence: 99%